2021
DOI: 10.3390/foods10071464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bran Pre-Treatment with Endoxylanase on the Characteristics of Intermediate Wheatgrass (Thinopyrum intermedium) Bread

Abstract: Previous work indicated that bran removal promotes network formation in breads prepared from intermediate wheatgrass (IWG) flour. However, refinement reduces yields as well as contents of nutritionally beneficial compounds such as fiber. This study evaluated xylanase pretreatment of IWG bran as a processing option to enhance the properties of bread made with half of the original bran content. Xylanase pretreatment did not affect stickiness but significantly reduced hardness and increased specific loaf volumes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The remarkable progress made toward IWG development and improvement has resulted in efforts to utilize IWG for mainstream food applications. Previous studies have focused on the compositional and functional properties of IWG as impacted by varietal differences, bran content, storage conditions, and dough conditioners to enhance baking quality (Banjade et al., 2019; Marti et al., 2016; Rahardjo et al., 2018; Tyl & Ismail, 2019; Zhong et al., 2019a), determining the starch hydrolysis kinetics of IWG (Zhong et al., 2019b), establishing tempering conditions for the production of refined IWG flour (Tyl et al., 2019), and pretreating IWG bran with xylanase to enhance the properties of IWG bread (Dai et al., 2021). In one such study (Tyl & Ismail, 2019), it was shown that IWG had higher protein, dietary fiber, and antioxidant contents than wheat.…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable progress made toward IWG development and improvement has resulted in efforts to utilize IWG for mainstream food applications. Previous studies have focused on the compositional and functional properties of IWG as impacted by varietal differences, bran content, storage conditions, and dough conditioners to enhance baking quality (Banjade et al., 2019; Marti et al., 2016; Rahardjo et al., 2018; Tyl & Ismail, 2019; Zhong et al., 2019a), determining the starch hydrolysis kinetics of IWG (Zhong et al., 2019b), establishing tempering conditions for the production of refined IWG flour (Tyl et al., 2019), and pretreating IWG bran with xylanase to enhance the properties of IWG bread (Dai et al., 2021). In one such study (Tyl & Ismail, 2019), it was shown that IWG had higher protein, dietary fiber, and antioxidant contents than wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the gas retention capacity during dough fermentation by Se-enriched yeast (87.15 ± 0.22%) was higher than that for the original yeast strain (83.96 ± 0.25%) ( p < 0.05). It is reported that yeast plays a certain role in increasing gluten extension in dough fermentation [ 25 ]. Whenever CO 2 is released by yeast metabolism, these gases will disturb surrounding molecules, which will increase the chance for protein molecules to contact with water molecules, so that glutenin in flour will be properly changed.…”
Section: Resultsmentioning
confidence: 99%
“…Images were captured using an HD camera (Canon, Japan, 1x). The analysis of stomatal morphology in cross-sections of bread is based on a previous study [ 25 ], with a slight modification. The images were processed using ImageJ version 1.50i (National Institute of Health, Rockville, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Another strategy to modify bran is via incubation with enzymes. Dai et al [ 7 ] focused their efforts on intermediate wheatgrass, a perennial grain of interest due to its considerable root mass, which may help counteract environmental challenges associated with intensive cereal production. However, the combination of weak protein networks and high fiber contents limits its use in baked goods.…”
mentioning
confidence: 99%
“…However, the combination of weak protein networks and high fiber contents limits its use in baked goods. Dai et al [ 7 ] used bran pre-treatment with xylanase to modify the fiber population, resulting in increased expansion, evidenced by higher specific volumes and differences in crumb structure. The effects on dough and bread were partially counteracted by ascorbic acid, added as a dough strengthener that also improved surface appearance.…”
mentioning
confidence: 99%